Estratégia de controle PI com adaptação fuzzy no acionamento elétrico por orientação de campo do motor de indução - SILVA, Paulo Ítalo Moreira da (2018)
We present in this dissertation a vector control strategy that employs a PI controller with an adaptation to fuzzy logic applied to the electric drive of a three-phase induction motor. The vector control strategy adopted is based on the indirect field orientation control (IFOC). The proposed strategy of vector control is used to control the high-performance speed of a three-phase induction motor of squirrel-cage rotor type. With the mathematical model obtained through IFOC strategy, current and speed PI controllers are developed, according to the project requirements. The fuzzy algorithm for the PI controller uses a rule base to generate adjustments referrals for gains of the PI controller, making possible for the PI controller to adapt their control parameters when subjected to various situations. The simulation results presented say to us that the control strategy used in this work is satisfactory, since the project requirements have been met.